New Record of Leptadenia arborea (Forssk.) Schweinf. in the Flora of Libya - Sh-Hoob M. El-Ahamir; Khaleefah S. Imohammed (Tunisian Journal of Plant Protection)
El-Ahamir, S.M. and Imohammed, K.S. 2024. New record of Leptadenia arborea (Forssk.) Schweinf. in the flora of Libya. Tunisian Journal of Plant Protection 19 (2): 63-68.